THE ROLE OF SOCIAL MEDIA IN PROMOTING VALUES RELIGION AT DARUL ARIFIN ISLAMIC BOARDING SCHOOL - Idris, Farah Amalia (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to explore the role of social media in promoting religious values at Darul Arifin Islamic Boarding School 2 Mangli Jember. In the midst of developments in information technology and globalization, Social media has become an important means of disseminating information and influence the thinking of the younger generation. In the context of religious diversity and complex culture, understanding religious moderation is crucial, especially for the younger generation as agents of social change. This research using a qualitative approach with case studies in Islamic boarding schools Darul Arifin 2 Mangli Jember. Qualitative data was analyzed using an approach thematic analysis. The sample was selected taking into account diversity and Islamic boarding school experience in using social media. Method data collection involves interviews, observation, and literature study.Results research shows that social media plays a key role in introduce and strengthen religious values. Islamic boarding school using various platforms such as Instagram, YouTube, and TikTok to live streaming of recitations, short videos, and promotional activities religious. The interactive role of social media enables direct dialogue with the audience, creating a deeper understanding of the teachings Islam.